HASIL BELAJAR KOGNITIF SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE AIR DAN NHT - Kamil, Idham; Kashardi, Kashardi (Jurnal Math-UMB.EDU, 2020)
This study aims to find out the significant differences between students' mathematical understanding abilities that are taught using the Cooperative Learning Model type Auditory Intellectualy Receptition (AIR), Numbered Heads Together (NHT), and conventional learning models, and which learning model gives better results to improve students' mathematical understanding abilities. This type of research is quasi-experimental. The population in this study was class VIII 27 of Seluma State Junior High School consisting of 4 classes. The sample of this study was chosen 3 classes randomly, namely class VIII A as the experimental class I using the Cooperative learning model type Auditory Intellectualy Receptition (AIR), class VIII B as the experimental class II using the cooperative learning model type Numbered Heads Together (NHT), and Class VIII C as a control class using conventional learning models. Data collection on student mathematics learning outcomes in the form of tests consisting of pre-test and post-test. Data were analyzed using ANAVA and BNT. Based on ANAVA results, there are differences between students' mathematics learning outcomes in experimental class I, experimental class II, and control class. Based on the LSD test it was found that the treatment between the experimental class I with the experimental class II, the experimental class I with the control class, and the experimental class II with the control class there were differences. Auditory IntellectualyReceptition (AIR) cooperative learning model provides better results than the Numbered Heads Together (NHT) type of cooperative learning model and Conventional learning model.Keywords: mathematical understanding ability, Â AIR,Â  NHT, learning model